2016
DOI: 10.1002/2015jg003316
|View full text |Cite
|
Sign up to set email alerts
|

Posteruptive impacts of pyroclastic deposits from basaltic andesite stratovolcanoes on surface water composition

Abstract: Volcanic ash deposition following explosive eruptions can pose significant hazards for water quality, human health, agriculture, and infrastructure functionality. Many studies have examined how fresh ash deposition may lower the pH of, and introduce a range of potentially toxic elements into, exposed surface waters. However, no study has yet determined the effects on water composition as a result of mechanical pyroclast disaggregation and production of new fresh particle surfaces and increasingly fine grained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 87 publications
(129 reference statements)
0
8
0
2
Order By: Relevance
“…The elevated EC values in the Akagawa River are attributed to the erosion, reworking, and entrainment of eruptive material and lahar deposits that contain minerals such as plagioclase feldspar and smectite (Kataoka et al 2018). These minerals contain sodium and calcium, and previous studies have demonstrated that these elements show a positive correlation with EC values in leachate experiments on pyroclastic deposits (Genareau et al 2016). Plagioclase is prone to chemical weathering (e.g., Nesbitt and Young 1996), and the acidity of the Akagawa River may have enhanced the dissolution of plagioclase grains.…”
Section: Differences In Post-eruption Fluvial Impact Between Catchmentsmentioning
confidence: 93%
“…The elevated EC values in the Akagawa River are attributed to the erosion, reworking, and entrainment of eruptive material and lahar deposits that contain minerals such as plagioclase feldspar and smectite (Kataoka et al 2018). These minerals contain sodium and calcium, and previous studies have demonstrated that these elements show a positive correlation with EC values in leachate experiments on pyroclastic deposits (Genareau et al 2016). Plagioclase is prone to chemical weathering (e.g., Nesbitt and Young 1996), and the acidity of the Akagawa River may have enhanced the dissolution of plagioclase grains.…”
Section: Differences In Post-eruption Fluvial Impact Between Catchmentsmentioning
confidence: 93%
“…The elevated concentrations of dissolved ions leached from volcanic ash, such as Cl, F, Al, Fe, Mn, As, Cd, Cr, Cu, Pb, Se, and Zn, can chemically alter the water, leading to a change in pH or toxic bioaccumulation, which can render the water unsafe for human and animal consumption (Flaathen & Gislason, 2007;Genareau et al, 2016;Stewart et al, 2006;Wilson et al, 2010). Certain metals are of particular concern for bioaccumulation because they may be toxic in low concentrations and do not degrade.…”
Section: Chemical Impactsmentioning
confidence: 99%
“…Volcanic ash eruptions produce well-known hazards, but the geochemical impacts on ecosystems and human health are not as well understood. Health hazards associated with volcanic eruptions include inhalation dangers and water contamination, which can lead to increased cancer risk, kidney damage, and skeletal and dental fluorosis (Baxter & Ancia, 2002;Genareau et al, 2016;Horwell et al, 2003;Ivhhn.org, 2018). After deposition and subsequent leaching in soils or water bodies, volcanic ash leachates may have both poisoning and fertilizing potential; by contaminating water and vegetation, making it unsafe for human and animal consumption, but also enriching volcanic soils with critical nutrients in the long term.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Son ecosistemas biogeoquímicamente muy activos debido al fuerte contacto entre la atmósfera, las riberas y el lecho bentónico (Liu et al 2008). Una característica hidromorfológica muy importante en este tipo de ecosistemas es el alto cociente entre el borde del arroyo y su área (Vannote et al 1980 (Genareau et al 2016).…”
Section: Introductionunclassified